Language of poetic composition for children (Eurasian Journal of Philology Science and Education, 2016)
The article reavels the theme about the role of language poetry for children. Literature for children – one of the literary currents in society.It‘ s birth the formation , the histpry of the development can njt be considered separatly from Kazakh Literature. Kazakh children’s poetryoriginats from folklore, which included besik–zhyry though patters and etc. With the child’s birth people connects hopes. Dreams with it. Their pomisty he puts into the poems and through the world trying to convey people’s values and to educate his generation. And every kid from the cradle hears the beauty of the songs and poems, lays the foundations of the humanrelations,educatesaethetic. Based on the forgiving, it can be argued that the work of children’s literature play an important role in group of children’s as individuals.
Keywords: Children’s literature; children’s poetry; children’s education; children’s poet; children’s writer of the Kazakh children’s Literature